An efficient terrain Level of Detail implementation for mobile devices and performance study. (July 2015) - Suárez, José P.; Trujillo, Agustín; Santana, José M.; de la Calle, Manuel; Gómez-Deck, Diego
Highlights: We present the problem of terrain rendering on handheld devices using remote data sources. It is presented our quadtree-based terrain representation and other implemented improvements. We analyze the memory/GPU impact of the adopted chunked LoD rendering system. Several experiments are performed showing the evolution of the triangle count depeding on the camera position. We analyze the performance of various flights running on iOS, Android and WebGL implementations. Abstract: On the basis of traditional Terrain Quadtree algorithms this paper introduces a new Level Of Detail (LoD) criteria which allows the visualization of a virtual earth on many kinds of mobile devices with a suitable accuracy. The earth rendering system is intended to run beneath the threshold that resources of current devices impose, regarding especially the graphics hardware capabilities and the memory usage. At the same time, the system deals flawless with typical screen-based user interaction allowing smooth flying and rapid orientation changes of the camera. The present work analyses the memory and graphics requirements from a theoretical perspective. Finally, we give a useful performance study that compares the globe on some mobile and desktop devices, focusing on LoD techniques, visibility test, creation of texture tiles, uploading tiles to GPU, and rendering.